After care without Relapse: Case Study Former Drug Dealer after Getting Therapy in Pondok Tetirah Dzikir (PTD) - Hendro Prabowo; Nur Aziz Afandi; Mahargyantari Purwani Dewi; Aski Marissa; Henny Regina Salve; Dinar Sari Eka Dewi (IJIP : Indonesian Journal of Islamic Psychology, 2022)
Abstract Pondok Tetirah Dzikir (PTD) is an Islamic boarding school for drug addicts from impoverished communities. These patients are classified as santri (students) and are eligible for six months of mental health services under TQN (Tarekat Qodiriyah Naqshbandiyah). The results of a case study on former drug dealers show that former drug addicts who have been rehabilitated at PTD have different characteristics than those who have been rehabilitated at other rehabilitation institutions. In comparison to other rehabilitation institutions, the subject never relapsed again after undergoing rehabilitation. This is due to the desire to do hijra, the desire to have a clear goal after rehabilitation, Dhikr with PTD alumni, friendship (silaturrahim) and mutual strengthening with PTD alumni, and aspirations as a penancer. Abstrak Pondok Tetirah Dzikir (PTD) merupakan pesantren bagi pecandu narkoba dari masyarakat kurang mampu. Pasien-pasien ini diklasifikasikan sebagai santri dan memenuhi syarat untuk layanan kesehatan mental selama enam bulan di bawah TQN (Tarekat Qodiriyah Naqsybandiyah). Hasil studi kasus pada mantan bandar narkoba menunjukkan bahwa mantan pecandu narkoba yang direhabilitasi di PTD memiliki karakteristik yang berbeda dengan mereka yang pernah direhabilitasi di lembaga rehabilitasi lainnya. Dibandingkan dengan lembaga rehabilitasi lainnya, subjek tidak pernah kambuh lagi setelah menjalani rehabilitasi. Hal ini disebabkan adanya keinginan untuk hijrah, keinginan untuk memiliki tujuan yang jelas setelah rehabilitasi, dzikir dengan alumni PTD, silaturrahmi (silaturrahim) dan saling menguatkan dengan alumni PTD, dan cita-cita sebagai penebus dosa.Kata Kunci: after care; pondok pesantren; tarekat qodiriyah naqsybandiyah